Trends in cancer incidence in Lithuania between 1991 and 2010 - Vincerževskienė, Ieva; Krilavičiūtė, Agnė; Smailytė, Giedrė (Acta medica Lituanica, 2014)
Background. Analysis of time trends in cancer incidence provides an estimate of the burden of cancer in a certain population and is a useful tool for planning cancer control. Identification of changing epidemiological patterns in cancer is crucial in formulating future healthcare clinical tools, evaluating prognostic and therapeutic models, and generating new hypotheses on disease aetiology and prevention. Materials and methods. Patients diagnosed with cancer in Lithuania between 1991 and 2010 were considered into analysis. Crude rates and age-standardized incidence rates for both sexes were calculated, as well as annual percent change with 95% confidence intervals for selected cancer sites using the Joinpoint Regression Analysis. Results. With the major exceptions of male lung cancer and stomach cancer in both sexes, cancer incidence has increased for most cancer sites in the last two decades in Lithuania. The strongest rises in incidence were seen for prostate cancer in men and thyroid cancer in women. Overall cancer incidence in men was strongly influenced by newly diagnosed prostate cancer cases. Conclusions. This up-to-date analysis provides a basis for establishing priorities to cancer control actions in Lithuania. These results show increase in incidence rates in Lithuania of all cancers combined among both men and women. Trends in cancer incidence rates for males were heavily influenced by trends in prostate cancer which is the most common cancer among men. Increasing cancer incidence requires targeted interventions on risk factors control, early diagnosis, and improved management and pharmacological treatment for selected cancer sites.